NK cells reduce anergic T cell development in early-stage tumors by promoting myeloid cell maturation - Lindsay, Robin S.; Melssen, Marit M.; Stasiak, Katarzyna; Annis, Jessica L.; Woods, Amber N.; Rodriguez, Anthony B.; Brown, Michael G.; Engelhard, Victor H. (Frontiers in Oncology, 2022)
Studies of NK cells in tumors have primarily focused on their direct actions towards tumor cells. We evaluated the impact of NK cells on expression of homing receptor ligands on tumor vasculature, intratumoral T cell number and function, and T cell activation in tumor draining lymph node. NK cells in early-stage tumors are one source of IFN that augments homing receptor ligand expression. More significantly, NK cell depletion resulted in increased numbers of intratumoral T cells with an anergic phenotype. Anergic T cell development in tumor draining lymph node was associated with increased T-cell receptor signaling but decreased proliferation and effector cell activity, and an incomplete maturation phenotype of antigen presenting cells. These effects of NK depletion were similar to those of blocking CD40L stimulation. We conclude that an important function of NK cells is to drive proper APC maturation via CD40L during responses to early-stage tumors, reducing development of anergic T cells.